The Impact of Risk and Resistance Factors on Quality of Life in Caregivers of Individuals with Dementia. Issue 5 (2nd September 2020) - Morrison, Blaise; Phillips, Brian N.; Jones, Jana E.; Przybelski, Robert; Huck, Garrett
ABSTRACT: Objectives: The present study investigates the effect of caregiver and care recipient risk and resistance factors on caregiver quality of life (QOL). Risk factors are those characteristics that contribute to psychosocial maladjustment of the caregiver and reduce QOL, while resistance factors promote caregiver adjustment and improve QOL. Methods: One-hundred and three caregiver/care recipient dyads were recruited from a memory assessment clinic in Midwestern United States. Caregivers completed questionnaires estimating perceived social support, spirituality, social problem-solving, and care recipient functional dependence. Care recipients' results from the Mini-Mental State Examination and Animal Naming task were also collected. Results: In the final model, caregiver age, relationship type, social problem-solving, perceived social support, and care recipient functional dependence each accounted for a significant portion of variance in caregiver QOL. The final model accounted for 46.1% of the variance in caregiver QOL. Conclusion: Caregiver age, relationship type, social problem-solving, perceived social support, and care recipient functional dependence are important contributors to caregiver QOL. Further research is needed to specify which caregiver and care recipient characteristics are most important to caregiver QOL. Clinical Implications: Health professionals should assess caregiver problem-solving skills, social support, and care recipient functional dependence, as these may provide important information about caregiver QOL. Study results also suggest that caregiving has more of a negative impact on caregiver QOL for midlife adult caregivers compared to older adult caregivers, and appears to have a greater negative effect on spouses than on children.